Learn in your speed, with individual attention - Teachoo Maths 1-on-1 Class

Ex 7.2

Ex 7.2, 1

Ex 7.2, 2

Ex 7.2, 3 Important

Ex 7.2, 4

Ex 7.2, 5 Important

Ex 7.2, 6

Ex 7.2, 7 Important

Ex 7.2, 8

Ex 7.2, 9

Ex 7.2, 10 Important

Ex 7.2, 11 Important

Ex 7.2, 12 You are here

Ex 7.2, 13

Ex 7.2, 14 Important

Ex 7.2, 15

Ex 7.2, 16

Ex 7.2, 17

Ex 7.2, 18

Ex 7.2, 19 Important

Ex 7.2, 20 Important

Ex 7.2, 21

Ex 7.2, 22 Important

Ex 7.2, 23

Ex 7.2, 24

Ex 7.2, 25

Ex 7.2, 26 Important

Ex 7.2, 27

Ex 7.2, 28

Ex 7.2, 29 Important

Ex 7.2, 30

Ex 7.2, 31

Ex 7.2, 32 Important

Ex 7.2, 33 Important

Ex 7.2, 34 Important

Ex 7.2, 35

Ex 7.2, 36 Important

Ex 7.2, 37

Ex 7.2, 38 (MCQ) Important

Ex 7.2, 39 (MCQ) Important

Last updated at May 29, 2023 by Teachoo

Ex 7.2, 12 Integrate the function: (𝑥3 – 1)^(1/3) . 𝑥5 (𝑥3 – 1)^(1/3) . 𝑥5 Step 1: Let 𝑥3= 𝑡 Differentiating both sides 𝑤.𝑟.𝑡.𝑥 3𝑥^2= 𝑑𝑡/𝑑𝑥 3𝑥^2. d𝑥=𝑑𝑡 𝑑𝑥 = 𝑑𝑡/(3𝑥^2 ) Step 2: Integrating the function ∫1▒〖" " (𝑥3 – 1)^(1/3) . 𝑥5" " 〗 . 𝑑𝑥 Putting the value of 𝑥^3 & 𝑑𝑥=𝑑𝑡/(3𝑥^2 ) = ∫1▒〖" " (𝑡 – 1)^(1/3) . 𝑥5〗 . 𝑑𝑡/(3𝑥^2 ) = ∫1▒〖" " (𝑡 – 1)^(1/3) . 𝑥^2. 𝑥^3 〗. 𝑑𝑡/(3𝑥^2 ) = ∫1▒〖" " (𝑡 – 1)^(1/3) 〗 . 𝑥^3/3 . 𝑑𝑡 = ∫1▒〖" " (𝑡 – 1)^(1/3) 〗 . 𝑡/3 . 𝑑𝑡 = 1/3 ∫1▒〖" " (𝑡 – 1)^(1/3) 〗 . 𝑡 . 𝑑𝑡 = 1/3 ∫1▒〖" " (𝑡 – 1)^(1/3) 〗 . (𝑡−1+1) 𝑑𝑡 = 1/3 ∫1▒〖" " (𝑡 – 1)^(1/3) 〗 . ((𝑡−1)+1) 𝑑𝑡 = 1/3 ∫1▒((𝑡 – 1)^(1/3) (𝑡−1)+(𝑡−1)^(1/3) ) 𝑑𝑡 = 1/3 ∫1▒((𝑡 – 1)^(1/3 +1)+(𝑡−1)^(1/3) ) 𝑑𝑡 = 1/3 ∫1▒((𝑡 – 1)^(4/3 )+(𝑡−1)^(1/3) ) 𝑑𝑡 = 1/3 ∫1▒〖 (𝑡 – 1)^(4/3 ). 𝑑𝑡〗 + 1/3 ∫1▒〖 (𝑡 – 1)^(1/3 ). 𝑑𝑡〗 = 1/3 ∫1▒〖 (𝑡 –1)^(4/3 ). 𝑑𝑡〗 + 1/3 ∫1▒〖 (𝑡 –1)^(1/3 ). 𝑑𝑡〗 = 1/3 (𝑡 –1)^(4/3 + 1)/(4/3 + 1) + 1/3 (𝑡 –1)^(1/3 + 1)/(1/3 + 1) + 𝐶 = 1/3 (𝑡 − 1)^(7/3)/(7/3) + 1/3 (𝑡 − 1)^(4/3)/(4/3) + 𝐶 = 1/7 (𝑡−1)^(7/3) +1/4 (𝑡−1)^(4/3) +𝐶 = 𝟏/𝟕 (𝒙^𝟑 –𝟏)^(𝟕/𝟑) + 𝟏/𝟒 (𝒙^𝟑–𝟏)^(𝟒/𝟑) + 𝑪